The impact of COVID-19 on self-reported burnout and health and mental health services in Nampula, Mozambique - Feliciano, Paulino; Mootz, Jennifer J.; Suleman, Antonio; Su, Austin Y.; Khan, Saida; Gouveia, Lidia; Santos, Palmira; Wainberg, Milton L.; Sweetland, Annika C. (Frontiers in Public Health, 2022)
Background The purpose of this study was to examine the impact of the COVID-19 pandemic on self-reported burnout of health workers, quality of care, and perceptions of COVID-19-related stigma in Mozambique. Method We conducted a cross-sectional quantitative assessment of 170 frontline health workers in Nampula District, Mozambique, including 149 (87.6%) primary care providers and 21 (12.4%) mental health specialists. Results Of the 170 frontline workers, only 10.1% of frontline workers were experiencing more professional burnout, whereas 33.3% felt it had lessened. The perceived impact on quality of care also varied, without any significant differences by sex, education level, or mental health training background. Compared to the beginning of the COVID-19 pandemic in March 2020, 42.3 and 38.1% providers felt that their ability to provide mental health and general health care, respectively, had worsened, compared to 57.7 and 61.9% who believed that either there was no change, or that the work had become easier. Likewise, 26.8% of providers felt that their ability to meet patients' needs had gotten more difficult, whereas 43.4% reported no change and 29.8% reported that it was easier. Twenty-two percent of providers reported an overall increase in caseloads since before the pandemic whereas the majority (67.9%) reported a decrease. Providers believed that 57.1% of people in general were afraid of people with COVID-19, 27.5% were afraid of a person recovered from COVID-19, and 39.9% were afraid of a person with family members with COVID-19. The perceived stigma about healthcare professionals was also low; only 27.4% believed that people in general were afraid of healthcare providers who deliver care to people with COVID-19. Conclusion In contrast with other global studies, many healthcare workers in our sample reported a reduction in burnout, which may be associated with the lower overall caseloads seen during this period. Similarly, the quality of care was minimally impacted. More research is needed to determine whether the experience in Mozambique is unique, or similarly observed in other low-resource settings.